Fast NMR method to probe solvent accessibility and disordered regions in proteins - Faustino, André F. (2019)
This work was supported by Fundacao para a Ciencia e a Tecnologia - Ministerio da Ciencia, Tecnologia e Ensino Superior (FCT-MCTES, Portugal) projects PTDC/QUI-BIQ/112929/2009, PTDC/SAU-ENB/117013/2010 and PTDC/BBB-BQB/3494/2014, Calouste Gulbenkian Foundation (FCG, Portugal) project Science Frontiers Research Prize 2010, European Union Marie Sklodowska-Curie Research and Innovation Staff Exchange H2020-MSCA-RISE-2014 project INPACT (Grant 644167), Conselho Nacional de Desenvolvimento Cientifico e Tecnologico (CNPq, Brazil, grant numbers 471239/2012-7 and 306669/2013-7) and Fundacao Carlos Chagas Filho de Amparo a Pesquisa do Estado do Rio de Janeiro (FAPERJ, Brazil, grant numbers E-26/110.636/2012, E-26/110.092/2013 and E-26/201.167/2014). AFF acknowledges FCT-MCTES fellowship SFRH/BD/77609/2011. MS acknowledges FCT-MCTES fellowship PD/BD/128202/2016. ICM acknowledges consecutive funding from the FCT-MCTES fellowship SFRH/BPD/74287/2010 and the Program "Investigador FCT" (IF/00772/2013 Research Contract). This work was also supported by LISBOA01-0145-FEDER-007391 project, cofunded by FEDER, through POR Lisboa 2020 -Programa Operacional Regional de Lisboa, PORTUGAL 2020, and Fundacao para a Ciencia e a Tecnologia. The NMR spectrometers at FCT NOVA are part of Rede Nacional de RMN (PTNMR), supported by FCT-MCTES (ROTEIRO/0031/2013 - PINFRA/22161/2016) co-funded by FEDER through COMPETE 2020, POCI, and PORL and FCT through PIDDAC.